Analisa Perbandingan BBM (Bahan Bakar Minyak) Dari Limbah Plastik Menggunakan Alat Pirolisis Pemanas LPG (Liquified Petroleum Gas) dan Listrik - Rozikin, Miftachur; Balaka, Ridway; Hasbi, Muhammad (Teknik Mesin Universitas Halu Oleo, 2020)
The purpose of this research is to know the comparison of fuel (oil fuel) pyrolysis results using LPG heaters (Liquid Petroleum Gas) and electricity. In this study using two pyrolysis tools, namely pyrolysis tools using gas and electrical heaters. Materials used are plastic garbage types of HDPE, LDPE and PP as much as 500 grams. The results of this study showed the value of the density of pyrolysis tools using gas heaters of 790.6 Kg/m³ for HDPE plastic, 722.0 Kg/m³ for LDPE Plastics and 738.7 Kg/m³ for PP Plastics. As for the viscosity value of 0.7853 m²/s for HDPE plastic, 0.6771 m²/s for LDPE Plastics and 0.6159 m²/s for PP Plastics. For the value of density by using the electrical pyrolysis tools are 771.4 Kg/m³ for HDPE plastic, 743.1 Kg/m³ for LDPE Plastics and 768.3 Kg/m³ for PP Plastics. While the viscosity value is obtained at 0.7198 m²/s for HDPE plastic, 0.7613 m²/s for LDPE and 0.7054 m²/s for PP plastic. Keywords: Pyrolysis, comparison of pyrolysis tools, plastics